Perencanaan Rute Distribusi Produk Pupuk NPK Blending Dengan Menggunakan Algoritma Differential Evolution Di PT. XYZ - Sholihin, Qouman; Donoriyanto, Dwi Sukma (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
This study aims to obtain an efficient distribution route to produce an optimal total mileage. The research was conducted at PT. XYZ which is one of the fertilizer producers in Sidoarjo, East Java. During the Covid-19 pandemic, the company experienced a decline in demand, so it was necessary to plan distribution routes based on fleet capacity. This research is focused on NPK Blending fertilizer products due to the high interest from the market and the company's frequent production and distribution of these products. The company distributes products to 42 buffers spread across East Java. The number of buffers results in many routes that must be passed so that companies need to do careful planning to produce optimal routes. So far, the company does not have the right method for planning distribution routes. In solving this problem, the researcher uses the differential evolution algorithm method. The company has 17 distribution routes with a total mileage of 4791,2 km, while the results of data processing using the differential evolution algorithm obtained 9 distribution routes with a total distance of 3594,4 km and obtained a mileage savings of 26% so that the use of the differential evolution algorithm can provide a more optimal distribution route. from the company route.Keywords – Distribution, Differential Evolution Algorithm, Vehicle Routing Problem